The effects of glucose, nitrate, and pH on cultivation of Chlorella sp. Microalgae - H. Nouri; J. Mohammadi Roushandeh; A. Hallajisani; A. Golzary; S. Daliry (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Bioenergy is a phenomenon that has attracted humans’ attention for about a century. The desirable biological properties of chlorella sp.microalgae have turned it to one of the most ideal options for the production of biodiesel. However, the economic issues must be taken into account in its industrial scale production. The present study aims to investigate chlorella sp. biomass production and growth conditions by studying the influence of glucose concentration as a carbon source, nitrate concentration as a nitrogen source and pH, as three of the most important factors. METHODS: For this purpose, design of experiment was done by response surface methodology and each factor was investigated simultaneously under glucose concentration in 2-20 g/L, nitrate concentration in 0-1 g/L and 6FINDINGS: The results indicated that carbon concentration has maximum effect on growth and biomass production. The best results were obtained in glucose concentration of 2.6-6 g/L, nitrate concentration of 0.2-0.5 g/L and pH values 7-9. Moreover, the maximum biomass production (1.31 g/L), the highest specific growth rate (0.167 1/day), and the highest biomass productivity (0.085 g/L/Day) were obtained in the following conditions: glucose concentration of 2.6 g/L, nitrate concentration of 0.5 g/L, and pH = 8. The optimal C/N ratio was determined and significant correlation was observed between pH and growth rate change. CONCLUSION: It was concluded that Chlorella sp < /em>., if properly adjusted for both chemical and physical parameters could be a valuable source of biomass for biodiesel production in industrial scale.